An overview of hydrogen storage technologies – Key challenges and opportunities - Mulky, Lavanya; Srivastava, Shashwat; Lakshmi, Thillai; Sandadi, Eashan Reddy; Gour, Santusti; Thomas, Noel Abraham; Priya, S. Shanmuga; Sudhakar, Kumarasamy (Elsevier, 2024)
Hydrogen energy has been proposed as a reliable and sustainable source of energy which could play an integral part in demand for foreseeable environmentally friendly energy. Biomass, fossil fuels, waste products, and clean energy sources like solar and wind power can all be employed for producing hydrogen. This comprehensive review paper provides a thorough overview of various hydrogen storage technologies available today along with the benefits and drawbacks of each technology in context with storage capacity, efficiency, safety, and cost. Since safety concerns are among the major barriers to the broad application of H2 as a fuel source, special attention has been paid to the safety implications of various H2 storage techniques. In addition, this paper highlights the key challenges and opportunities facing the development and commercialization of hydrogen storage technologies, including the need for improved materials, enhanced system integration, increased awareness, and acceptance. Finally, recommendations for future research and development, with a particular focus on advancing these technologies towards commercial viability.